A perfect day for digging - Best, Cari (Two Lions, 2014)
In the spring when trees unfreeze and grass grows green and pansies say, "Please plant me!" Nell and her dog, Rusty, can't wait to dig in dirt just right for digging. But Norman, their neighbor, says "Ewww!" to digging and dirt.